COMMISSIVE UTTERANCES IN KUNG FU PANDA 2 MOVIE AND THEIR FUNCTIONS - Kristina Desenta Wimmy Putri; Yuli Widiana (Humaniora Scientia, 2022)
The research aimed to find out and classify the types of commissive speech acts used by the characters in Kung Fu Panda 2 Movie. The study explained the functions of each type of commissive speech act based on the contexts as well. The method applied was the descriptive qualitative method. The data of this research were in the form of words, phrases, clauses, and sentences that contain commissive speech acts. Hereafter, the technique of data analysis was based on Kreidler's (1998) classification of commissive speech acts. The next step was explaining the functions of each type of commissive speech acts based on the pragmatic contexts. The research found seven types of commissive speech acts used by the characters in the movie of Kung Fu Panda 2, such as promises, pledges, agrees, refuses, volunteers, offers, and threats. The most dominant type of commissive speech act used by the characters was the act of agreeing. The least type of commissive speech act used by the characters was the act of pledging.Keywords: Pragmatics, speech acts, commissive utterances